Accommodating low proficiency esl students’ language learning needs through an online writing support system - David, Anne Rowena; Siew, Ming Thang; Hazita Azman (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
This article shares the personal experiences of a teacher–researcher (TR) in accommodating the language learning needs of a group of low proficiency English as Second Language (ESL) undergraduates at a local public university in Malaysia through the introduction of an online writing support system. Research studies have shown that low proficiency ESL students lack motivation and determination towards improving their language proficiency, especially their writing skills (Hsu & Chuen, 2008). Hence, they need to be supported in their language learning processes. In order to find appropriate ways to do this, the TR conducted a needs analysis survey to gather information about their language needs. The data analysis revealed that students found writing to be the most difficult and complex skill to master among the four language skills. Thus, to help them, the TR designed an online writing support system using the e-learning platform of the university to support them. In relation to this, this paper will first report on the findings obtained from the needs analysis and then explain how the online writing support system will help to cater to these needs.